2005
DOI: 10.1002/dc.20231
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of trichomonas vaginalis in liquid-based Pap tests: Morphological characteristics

Abstract: We investigated the morphological features of Trichomonas vaginalis in liquid-based Papanicolaou (Pap) (LBP) tests, in order to assess the impact of this new slide preparation system on recognition of T. vaginalis organisms. We reviewed 88 LBP test slides previously interpreted as showing T. vaginalis and assessed morphological characteristics of the organisms and the presence of secondary features. Eighty-six of 88 slides showed, at least focally, organisms with cytoplasmic granules, nuclei, and flagella allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…We therefore believe that this improved pick-up rate is most likely explained by the better visualization of the HSVrelated cellular changes by the reduction or elimination of obscuring by inflammation and blood in LBPT, factors that have also improved the identification of squamous abnormalities, 47 Candida, 48 and T. vaginalis. 49,50 Contrary to our findings, no significant differences between the HSV detection rates between Thinprep LBPTs (68/ 190,667, 0.036%) and CPSs (62/194,281, 0.032%) were found by a recent large study from Hong Kong. 44 This difference may be related to the different types of LBPT used (Surepath vs. Thinprep) or to other methodological differences between the two studies.…”
Section: Discussioncontrasting
confidence: 86%
“…We therefore believe that this improved pick-up rate is most likely explained by the better visualization of the HSVrelated cellular changes by the reduction or elimination of obscuring by inflammation and blood in LBPT, factors that have also improved the identification of squamous abnormalities, 47 Candida, 48 and T. vaginalis. 49,50 Contrary to our findings, no significant differences between the HSV detection rates between Thinprep LBPTs (68/ 190,667, 0.036%) and CPSs (62/194,281, 0.032%) were found by a recent large study from Hong Kong. 44 This difference may be related to the different types of LBPT used (Surepath vs. Thinprep) or to other methodological differences between the two studies.…”
Section: Discussioncontrasting
confidence: 86%
“…However, halos cells were more frequent in SurePath (92%) than in Cytyc (90%), and cannonballs and squamous metaplasia were more frequent in Cytyc (93% and 63%, respectively) than in SurePath (88% and 51%, respectively) but did not reach significance (p > 0.05) (Table II). In the present study, in accordance with the data published by Aslan et al, 14 we confirmed that liquid-based cytology is an effective and accurate technique to detect T vaginalis infection. In addition, the SurePath and Cytyc techniques, which are the most commonly used liquid-based cytologic techniques, have similar efficacy for the detection of this type of infection.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the suburban population included was the same type as in the Aslan et al study. 14 Among the morphologic criteria associated with T vaginalis infection, we found a significant difference in frequency between the 2 techniques of liquid-based cytology. Thus, we found that ghost cells were significantly more commonly associated with Trichomonas in SurePath 79/88 (89%) than in Cytyc 38/80 (48%) (p = 0.00001).…”
Section: Discussionmentioning
confidence: 82%
“…The diagnosis of Trichomonas was based upon the presence of a discernible nucleus and cytoplasmic granules that were identified in several of the trichomonads. A visible nucleus and well-defined cytoplasmic granules at 40x magnification are specified as important morphological features required for a confident diagnosis of Trichomonas in liquid-based Pap tests [1]. Although we did not identify flagella in the trichomonads in our case, the finding of flagella, while helpful, is not always required to make a diagnosis of Trichomonas [1].…”
Section: Articlementioning
confidence: 85%
“…A visible nucleus and well-defined cytoplasmic granules at 40x magnification are specified as important morphological features required for a confident diagnosis of Trichomonas in liquid-based Pap tests [1]. Although we did not identify flagella in the trichomonads in our case, the finding of flagella, while helpful, is not always required to make a diagnosis of Trichomonas [1]. In fact, the morphologic identification of Trichomonas on liquid-based Pap tests has been shown to be highly accurate [2].…”
Section: Articlementioning
confidence: 99%